A Structural Analysis of Supplier Selection Criteria: Implications for Digital Seller Prioritization and Company Performance In E-Commerce Environments - Topdemir, Ramazan; Akman, Gülşen (International Journal of Industrial Engineering: Theory, Applications and Practice, 2026)
Effective supplier selection in e-commerce requires understanding the complex criteria interdependencies that drive company performance. This study addresses this gap by developing a structural framework using a Multiple Criteria Decision Making (MCDM) approach. We integrate the Delphi method with a panel of eight industry experts with Interpretive Structural Modeling (ISM) and Cross-Impact Matrix Multiplication Applied to a Classification (MICMAC) analysis to map these critical relationships. The research suggests a seven-level hierarchy that challenges traditional cost-focused evaluations. Foundational criteria like quality, customer service, and manufacturer status are identified as the system’s primary drivers, while financial metrics such as price and cost are suggested to be dynamic outcomes. This study proposes a conceptual framework for managers, suggesting a strategic shift from tactical cost-cutting to prioritizing foundational drivers for sustainable business success.